Research Designs and Statistical Methods Trends in the Annals of Rehabilitation Medicine - Kim, Jinmo; Yoon, Seihee; Kang, Jung Joong; Han, Kyunghwa; Kim, Jong Moon; Kim, Shin Kyoung (Annals of rehabilitation medicine, 2017)
To investigate trends of the research designs and statistical methods in the (ARM) published from 2005 to 2015 through a comparison of articles with the (APMR). The authors reviewed all articles published in ARM and APMR for the years 2005 and 2015 in order to determine their research designs as well as their statistical methods used in each article. In ARM, randomized controlled trials increased from 4.5% in 2005 to 6.5% in 2015. In APMR, randomized controlled trials increased from 8.1% in 2005 to 14.0% in 2015, meta-analyses increased to 5.3%, and systematic reviews increased to 6%. The number of studies using statistical methods increased in ARM from 1.9 to 2.6 per article and in APMR, from 2.7 to 3.1. Use of advanced methods in ARM also showed an increase from 2005 to 2015. This study concludes that there is a trend of increased awareness and attempts to use varied research approaches in ARM articles. There should also be more in-depth discussions and opportunities for researchers to share their experiences regarding statistical methods in the clinical field.